(untitled) (Research, Society and Development, 2026)
This article aims to understand how the use of digital technologies in Brazilian Indigenous schools influences the teaching-learning process, analyzing its contribution to expand access to knowledge and strength pedagogical practices, without disregarding traditional cultural knowledge. The research was developed through a qualitative bibliographic review based on the analysis of recent scientific studies that address the relationship between connectivity, Indigenous school education, and cultural preservation. From the survey and analysis of ten articles selected from academic databases, the study sought to identify the main contributions and challenges related to the integration of digital technologies in the Indigenous educational context. The results indicate that the internet can expand methodological possibilities in the school environment, facilitate access to information, and contribute to the appreciation and documentation of traditional knowledge. However, the studies also highlight significant challenges, such as infrastructure limitations, inequalities in access to connectivity, and the need for adequate teacher training for the pedagogical use of technologies. It is concluded that digital technologies and connectivity, when integrated in a critical, contextualized, and intercultural way, can act as important tools to support Indigenous education, contributing simultaneously to cultural strengthening and to the expansion of educational opportunities.